VO #021.1 Extra proposal of additional wall of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding VO #021.1 extra proposal of additional wall of BRAC University new campus project.